Free Tissue Transfer in Pediatric Lower Limb Trauma - Srikanth, R. (Indian Journal of Plastic Surgery, 2019)
Free tissue transfer has become the standard in wound coverage and further refinements have given us newer flap donor sites or modifications of existing flaps to decrease morbidity; smaller vessels are being anastomosed, a direct spin-off following successful distal replantations. Younger children are presenting with traumatic defects similar to adults. Although there were apprehensions of free tissue transfer in children occasioned by smaller vessels, duration of procedure and concerns of growth following flap harvest, reports of small and large series have appeared in the literature with similar success. Pediatric-free tissue transfer is now an established entity. This article seeks to arrive at a consensus based on a review of the existing literature on free flaps for skin and soft-tissue coverage of lower limb trauma in children.
Keywords: free flaps; lower limb trauma; pediatric